Cloning and purification of recombinant proteins of Mycoplasma hyopneumoniae expressed in Escherichia coli - Simionatto, Simone; Marchioro, Silvana B.; Galli, Vanessa; Hartwig, Daiane D.; Carlessi, Rodrigo M.; Munari, Fernanda M.; Laurino, Jomar P.; Conceição, Fabricio R.; Dellagostin, Odir A. (Protein expression and purification, 2010)
Mycoplasma hyopneumoniae, the etiological agent of swine enzootic pneumonia, is an important pathogen in the swine industry worldwide. Vaccination is the most cost-effective strategy for controlling and prevention of this disease. However, investigations on pathogenicity mechanisms as well as current serological detection methods and the development of new recombinant subunit vaccines are hampered by the lack of known and well characterized species-specific M. hyopneumoniae antigens. In this work, 54 predicted genes encoding proteins with potential to be used as subunit vaccine or antigens in diagnostic tests were selected, amplified by PCR and cloned into Escherichia coli expression vectors. Recombinant protein expression, solubility and yields were analyzed. The majority of the recombinant proteins were expressed in inclusion bodies. After solubilization with urea or N-lauroyl sarcosine, recombinant proteins were purified by Ni 2+ affinity chromatography. This approach allowed purification of thirty recombinant M. hyopneumoniae proteins which will be evaluated as vaccine candidates and/or as antigens to be used in diagnostic tests.